Primary Renal Carcinoid Metastatic to the Orbit. Issue 2 (March 2015) - Parikh, Deep; Shinder, Roman
<x xml:space="preserve">Abstract</x> A 70-year-old man with a medical history of metastatic renal carcinoid tumor presented with several months of painless proptosis of the OS. The patient was receiving octreotide and everolimus chemotherapy. MRI revealed a well-circumscribed mass in the left lateral rectus muscle consistent with metastasis. Because the patient was asymptomatic, he was observed and maintained a stable amount of proptosis without diplopia or change in vision.